2017
DOI: 10.1002/arch.21384
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals isolated from Justicia adhatoda Linn reduce fitness of the mosquito, Aedes aegypti L

Abstract: Extracts from Justicia adhatoda L. (Acanthaceae) strongly reduced the fitness of the mosquito, Aedes aegypti Linn. The methanolic extracts inhibited several enzymes responsible for protecting insects from oxidative and other damage, including glutathione-S-transferase, superoxide dismutase, cytochrome P450, and α- and β-esterases. They increased repellency (maximum repellency at 100 ppm) in host-seeking adult females using the "arm-in cage assay." Histopathological examination showed the extracts led to seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Many previous research outcomes proved alteration or inhibition in the expression of major detoxifying enzymes exposed to plant chemicals. Thanigaivel et al (2017a) showed increase in the rate of GST activity in IV instar larvae of dengue mosquito exposed to methanolic leaf extract of J. adhatoda with their major derivative 3-hydroxy-2,3-dihydropyrrolo[2,1-b]quinazolin-9(1h) one (26.37%). Likewise, carboxylesterase activities differed significantly in Ae.…”
Section: Impact Of Phytochemicals On Detoxifying Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous research outcomes proved alteration or inhibition in the expression of major detoxifying enzymes exposed to plant chemicals. Thanigaivel et al (2017a) showed increase in the rate of GST activity in IV instar larvae of dengue mosquito exposed to methanolic leaf extract of J. adhatoda with their major derivative 3-hydroxy-2,3-dihydropyrrolo[2,1-b]quinazolin-9(1h) one (26.37%). Likewise, carboxylesterase activities differed significantly in Ae.…”
Section: Impact Of Phytochemicals On Detoxifying Enzymesmentioning
confidence: 99%
“…A study conducted on testing the mosquitocidal activity of Justicia adhatoda L. (Acanthaceae) leaf extracts revealed the potential of natural larvicidal agent against Ae. Aegypti (Thanigaivel et al, 2012(Thanigaivel et al, , 2017a.…”
Section: Biological Management Of Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to gage the primary and secondary impact of any forms of pesticides upon non-target species [26,31,51]. Toxorhynchites are an excellent predator against the dengue larvae 'Aedes' and are measured to be not hurtful to their well-beings and well-fixed as they are non-blood feeders and considered to be a good biological predator for reducing the populations of blood-sucking mosquitoes [52].…”
Section: Discussionmentioning
confidence: 99%
“…The prepared enzyme homogenates were prepared based on our previous research [15] and kept on ice for further enzyme assays. Furthermore, enzyme estimations of carboxylesterase (α and β), SOD, glutathione S-transferase (GST), and CYP450 were analyzed based on the adapted methodology of Thanigaivel et al [26].…”
Section: Enzyme Assaysmentioning
confidence: 99%